Transcendental vs. comparative approaches to justice: a reappraisal of Sen's dichotomy. Issue 4 (3rd July 2016) - Ege, Ragip; Igersheim, Herrade; Le Chapelain, Charlotte
Abstract: In The Idea of Justice, Sen describes two competing approaches to theorising about justice: "transcendental institutionalism", in which he includes Rawls, and "realisation-focused comparison", in which he includes Condorcet and himself. The objective of this paper is to demonstrate that a comparative approach cannot exist without a transcendental dimension. Contrary to Sen, who claims that a transcendental theory is neither necessary nor sufficient in order to frame comparative judgments, it is shown that a transcendental dimension is a necessary, albeit not sufficient, condition of any comparative approach. To illustrate our thesis, we refer to the works of three great authors: Condorcet, Sen himself and the later Rawls.